Errata and authorial handwritten corrections in Michel de Vascosan’s edition of the Latin translation of Aristotle’s Politics by Juan Ginés de Sepúlveda (Paris, 1548) - Solana Pujalte, Julián; García Pinilla, Ignacio J. (Cuadernos de Filología Clásica. Estudios Latinos, 2012)
This paper studies the large number of misprints inMichel de Vascosan’s edition of the Latin translation, by Juan Ginés de Sepúlveda, ofAristotle’s Politics (Paris, 1548). The author, deeply disappointed, marked them in two different copies. They were planned to be used in the preparation of a new edition of the work, never printed.
Keywords: Juan Ginés de Sepúlveda; Aristotle’s Politics; Aristoteles latinus; Michel de Vascosan; Textual criticism.